Improved rainfall thresholds for index insurance in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Weather shocks can trap farmers and households in poverty. At the same time, the risk of such shocks occurring often discourage farmers from trying out innovations, such as new types of seed or different technologies, which could increase productivity and resilience. Conventional crop insurance relies on the direct assessment of an individual farmer’s loss or damage, but carrying out field assessments in developing countries is often time consuming and costly. Weather index insurance, on the other hand, is based on objective thresholds such as rainfall amounts or temperatures measured at defined locations. Based on the requirements of the crop being insured, a threshold is selected above or below which payouts are made. This means it is not necessary to assess every insured farmer’s loss. In this way, weather index insurance enables farmers to insure their crops against weather risk in areas where traditional agricultural insurance is not available.